PENGARUH SENAM YOGA TERHADAP PENURUNAN NYERI HAID PADA REMAJA PUTRI DI INSTITUT KESEHATAN MITRA BUNDA - Desi Ernita Amru; Anisya Selvia (Midwifery Care Journal, 2022)
Adolescence is marked by changes in body development associated with puberty. In this condition, women will experience ovulation and menstruation which is sometimes accompanied by menstrual pain (dysmenorrhea). This condition can get worse when accompanied by unstable psychological conditions, such as stress, depression, excessive anxiety, and excessive sadness or joy. The purpose of this study was to determine the effect of yoga exercise on reducing menstrual pain in adolescent at the Mitra Bunda Health Institute. The type of this research is pre-experimental with one group pretest posttest design. The population of this study was all students of the Midwifery Undergraduate Study Program at the Mitra Bunda Health Institute with a total of 75 students. The sample of this study was 75 female students with a total sampling technique. The independent variable is Yoga Gymnastics and the dependent variable is Menstrual Pain. The research instrument uses the Face Pain Scale – Revised (FPS-R) pain scale measurement. Data processing using editing, coding, scoring, tabulating with data analysis Spearman Rank. The results showed that before doing yoga exercise there were 46 respondents (61.3%) experiencing menstrual pain on a scale of 3 (more painful), while after yoga exercise there were 30 respondents (40%) experiencing menstrual pain on a scale of 1 (slight pain). Spearman rank statistical test shows that P value= 0,000 α (0,05). So that H1 is accepted, it means that there is an effect of yoga exercise on reducing menstrual pain in adolescent girls at the Mitra Bunda Health Institute, Batam. Suggestions for respondents are expected to get used to doing yoga to reduce menstrual pain so as not to depend on analgesic drugs every menstruation.